Pengaruh Penggunaan Microsoft Office Terhadap Profesionalisme Guru Taman Kanak-Kanak - Dewanti, Salsabila Putri; Windiarti, Rina (Peneliti.net, 2023)
Technology is developing very rapidly in the digitalization era. Software of various types is created in tandem with the advancement of technology. One of them is the Microsoft Office application, which can be used in educational settings. Teachers are now expected to master technology and apply it in the classroom and school administration. As a result, the goal of this study was to collect information on the impact of Microsoft Office applications on the professionalism of Kindergarten (TK) teachers. This study used a quantitative method with cross sectional design. The population in this study were kindergarten teachers who followed Microsoft Office course at Vocasia with 16 sample. The data was collected through the distribution of questionnaires by Google Form. Then, the results of the research were processed by the normality test, regression analysis, and coefficient of determination. The results of the study indicated that using Microsoft Office applications had a 70.7% influence on teachers' professionalism. Furthermore, teachers could use the Microsoft Office application to manage school administration by creating Lesson Plans (RPP), recording student learning outcomes, creating innovative learning media, creating children's worksheets, managing financial administration, and compiling a learning curriculum. Thus, mastery of Microsoft Office applications is highly recommended for kindergarten teachers. Keywords: Microsoft Office, Professionalism, Kindergarten Teacher